A Comparative Study on the Microbial and Physicochemical Characterization of Borehole Water from Bonny and Omuku, Rivers State, Nigeria - Olasanmi, O.M; Onwukwe, C.D; Ikedimma C.M.; Ezeonuegbu, B.A (Archives of Current Research International, 2025)
This study investigated the microbial and physico-chemical quality of borehole water in Omoku and Bonny, Port Harcourt, Nigeria. A total of four borehole sites in duplicates were sampled from each sample community, where water samples were collected from different sample points and mixed to form a composite sample for a community and analyzed for physico-chemical parameters (pH, temperature, TDS, turbidity, hardness, alkalinity, chloride, nitrate, and sulfate) and microbial contaminants including total Coliforms and feacal Coliforms. The results showed varying levels of physico-chemical parameters and microbial analysis revealed the presence of pathogenic bacteria only in samples from Omoku while that of Bonny yielded no microbial growth. The total heterotrophic bacterial counts (THBC) from Omoku ranged from 3.2 x105 CFU/ml - 9.4 × 105 CFU/ml while the fungal counts ranged from 1.5 × 103 - 2.0 × 104. A total of 7 strains of bacteria and 4 fungal isolates were identified from the water samples from Omoku to generic level. Bacterial genera encouneterd included Staphylococcus sp., Enterobacter sp. and Proteus sp. Fungal isolates identified included Fusarium sp., Penicillium sp., Trichoderma sp. and Candida sp. The Most Probable Number (MPN) method for total coliform determination revealed counts for samples from Omoku community borehole (14 colonies/100ml each), highlighting the need for continued and sustained monitoring. Physicochemical parameters such as pH which revealed the water to be slightly acidic (6.79-6.86), nitrate ranged from 8.63 - 15.74mg/l, turbidity ranged from 0.53 - 1.22 ntu, TDS ranged from 1.67 - 1.83 mg/l and total hardness ranged from 93.87 - 158.85 mg/l. This study highlights the need for regular water testing, proper borehole construction and maintenance, and effective water treatment to ensure safe drinking water. The findings contribute to the development of sustainable water management strategies, promoting public health and environmental sustainability in urban Nigeria.